Prevalence and Factors Associated with Depression in Healthcare Personnel During the SARS-CoV-2 Pandemic in the Department of Piura, Peru - Espinoza-Ascurra, Gonzalo (2022)
Introduction: The COVID-19 pandemic has increased the magnitude of mental illnesses such as depression, not only in the general population, but also in healthcare personnel. However, in Peru the prevalence, and the associated factors for developing depression in healthcare personnel, are not known. The objective was to determine the prevalence and identify the factors associated with depression in healthcare personnel, in the context of the SARS-CoV-2 pandemic. Methods: An analytical cross-sectional study was carried out from May to September, 2020 in healthcare establishments. A sample of 136 health workers were included and a survey was applied to collect the data. Depression as a dependent variable was measured using the Zung self-report scale. To identify the associated factors, the bivariate and multivariate analysis was performed by logistic regression with STATA v 14. Results: The prevalence of depression was 8.8% (95%CI, 4.64-14.90). Having a family member or friend who had died from COVID-19 was associated with depression (OR = 6.78; 95%CI, 1.39-32.90; P = 0.017). Whereas the use of personal protective equipment was found to be a protective factor against developing depression (OR = 0.03; 95%CI, 0.004-0.32; P = 0.003). Conclusions: Approximately 1 in 10 healthcare professionals and technicians developed depression during the COVID-19 pandemic in this study. In addition, having relatives or friends who had died from COVID-19 was negatively associated with depression and use of personal protective equipment was identified as a protective factor.